2014
DOI: 10.1002/ejsp.2045
|View full text |Cite
|
Sign up to set email alerts
|

Pain reduces discrimination in helping

Abstract: Because of their shared neurobiological underpinnings, factors increasing physical pain can also increase feelings of social disconnection ("social pain"). Feelings of connection with a social group are reflected in the term social identification, and social identity is commonly associated with intergroup discrimination. In two experiments, we examined the notion that physical pain would reduce social identification and subsequently inhibit intergroup discrimination in helping. By using a pain memory manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This disruption of ordinary social goals is also borne out in laboratory studies, in which social biases appear to be overshadowed following physical pain. For instance, van Leeuwen, Ashton-James, and Hamaker (2014) found that physical pain (recalled and experienced) attenuated the in-group favoritism effect. They found that for participants in the pain condition, support and helping toward out-group members was no different to in-group members.…”
Section: Bringing It Together: Illustrating the Frameworkmentioning
confidence: 99%
“…This disruption of ordinary social goals is also borne out in laboratory studies, in which social biases appear to be overshadowed following physical pain. For instance, van Leeuwen, Ashton-James, and Hamaker (2014) found that physical pain (recalled and experienced) attenuated the in-group favoritism effect. They found that for participants in the pain condition, support and helping toward out-group members was no different to in-group members.…”
Section: Bringing It Together: Illustrating the Frameworkmentioning
confidence: 99%